Impact of the COVID-19 Pandemic on Social and Economic Families and Ability to Meet Daily Needs - Fitri Hayati (Pena Cendekia Insani, 2022)
The pandemic of COVID-19 has had a significant influence on the socioeconomic community, particularly Indonesia. High layoffs, reduced income, and higher household spending are the economic consequences. The goal of this research is to find out how the COVID-19 pandemic has affected social and economic families, as well as their ability to meet daily needs. This research employs a cross-sectional design and a quantitative descriptive technique. Data is collected via a Google form, and then bivariate data with The chi-square test. Study whow with the chi-square test revealed a link between deteriorating family income and the family's ability to meet daily demands (p0001). According to the findings of this study, families with a loss in family income were 6,178 times less likely to be able to meet daily demands than families who did not have a fall in family income. The COVID-19 epidemic has been shown to have an impact on family members' ability to meet their basic needs, particularly when family income falls.